2014
DOI: 10.1177/1060028014537897
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Associated With Prothrombin Complex Concentrate for International Normalized Ratio Reversal in Patients on Oral Anticoagulants With Acute Bleeding

Abstract: Three-factor PCC administration with IV vitamin K was effective for INR reversal and bleeding cessation and should continue to be a mainstay of therapy pending head-to-head outcome and cost comparisons with 4-factor products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The effect of vitamin K is seen only several hours after administration. The recommended dose of plasma for VKA reversal is 15 to 30 mL/kg and typically translates into a volume of 1000 to 2000 mL, which is rarely practical. Also, the time required to obtain a blood type, thaw, and prepare and then infuse the plasma can lead to significant delays in achieving the desired clinical effect.…”
mentioning
confidence: 99%
“…The effect of vitamin K is seen only several hours after administration. The recommended dose of plasma for VKA reversal is 15 to 30 mL/kg and typically translates into a volume of 1000 to 2000 mL, which is rarely practical. Also, the time required to obtain a blood type, thaw, and prepare and then infuse the plasma can lead to significant delays in achieving the desired clinical effect.…”
mentioning
confidence: 99%
“…This is supported by several other studies that demonstrated low rates of INR reversal when using Profilnine™ in patients with higher baseline INRs. 24,25,22,14 In our study, Bebulin™ still resulted in achieving goal INR in more patients when the exact same dosing regimen was used with both agents. Per package labeling, Bebulin™ (0.05-0.2 units of factor VII per unit of factor IX) 10 appears have a lower amount of factor VII than Profilnine™ (no more than 0.35 units of factor VII per unit of factor IX).…”
Section: Discussionmentioning
confidence: 63%
“…Two studies demonstrated higher efficacy (80% and 89%) when targeting goal INR of <1.4 and using an INR-based dosing regimen for Profilinine™ (25 U/kg used if INR <4.0 and 50 U/kg if 4.0 or higher). 21,22 The same Profilnine™ dosing regimen achieved goal in 100% of patients when using an INR target of 1.7. 23 When studying patients with baseline INR >5, Holland and colleagues found that Profilnine™ at 25 and 50 U/kg attained goal INR <3.0 in only 55% and 43% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%